Réponses

2014-02-18T16:25:49+01:00
A=4(x+3) 
4*x+4*3
4x+12

B=(2x+5)(x-8)
2x*x+2x*(-8)+5*x+5*(-8)
2x²-16x+5x-40
2x²-11x-40

C=2x(x-4)+8x
2x*x+2x*(-4)+8x
2x²-8x+8x
2x²

D=x(-x)
x*(-x)
-x²

E=3x+3-(x+5)(x-)
il manque un terme

F=(x+3)(x-3)-2(x-8)
x*x+x*(-3)+3*x+3*(-3)-2*x-2*(-8)
x²-3x+3x-9-2x+16
x²-2x+7
2014-02-18T16:33:15+01:00
Bonjour

A=4(x+3) = 4x +12
B=(2x+5)(x-8) = 2x² - 16x +5x -40 = 2x² - 11x -40
C=2x(x-4)+8x = 2x² - 8x +8x = 2x²
D=x(-x) = - x²
E=3x+3-(x+5)(x-) = manque un chiffre
F=(x+3)(x-3)-2(x-8)
= x² -3x +3x -9 -2x +16 = x² -2x +7